Russian traditions in modern television advertising (Mongolian Journal of Arts and Culture, 2024)
Russian traditions contain, directly, cultural information containing ideas about the picture of the world, human values, religious beliefs, and national potential. A feature that is characteristic of a modern advertising product is the search for the optimally fast way to memorize and reproduce advertising information by the consumer in order to purchase the advertised product. One of the main techniques used by advertising specialists is the use of existing working schemes in the advertising process. These are, first of all, folk traditions and archetypal ideas about them. Endowing commercials with primordial “Russianness” gives advertising works a special charm - they are viewed with pleasure by the audience, easily recognized, talked about, and most importantly, they are remembered without any problems and, if possible, even quoted by the audience of the commercial.Русские традиции в современной телевизионной рекламеАннотация: Русские традиции содержат в себе непосредственно культурную информацию, содержащую представления о картине мира, человеческих ценностях, религиозных верованиях, национальном потенциале. Характерной чертой современного рекламного продукта является поиск оптимально быстрого способа запоминания и воспроизведения рекламной информации потребителем с целью приобретения рекламируемого продукта. Одним из основных приемов, используемых специалистами по рекламе, является использование в рекламном процессе уже существующих рабочих схем. Это, прежде всего, народные традиции и архетипические представления о них. Наделение рекламных роликов исконной «русскостью» придает рекламным произведениям особое очарование — их с удовольствием смотрит аудитория, они легко узнаются, о них говорят, а главное, они без проблем запоминаются и, по возможности, даже цитируются аудиторией рекламного ролика.Ключевые слова: реклама, телевизионная реклама, традиция, обычай, рекламное сообщение, процесс коммуникации